2018
DOI: 10.1038/s41394-018-0065-8
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of a training program to enhance transformational leadership in Spinal Cord Injury Peer Mentors

Abstract: Research supported by a SSHRC Partnership Development Grant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…We interpreted Casey's approach as being consistent with a person-centered approach to mentoring by focusing their attention on the needs of the mentee. Using a personcentered focus is consistent with previous literature used person-centered theories, such as Self-Determination Theory [3,4] and Transformational Leadership [10,12] to understand SCI peer mentorship. Our results also extend findings from a small body of research focusing on the perspective of the peer mentor where Gainforth et al [11] and Shaw et al [13] highlighted that effective peer mentors appear to adopt a person or client-centered approach.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…We interpreted Casey's approach as being consistent with a person-centered approach to mentoring by focusing their attention on the needs of the mentee. Using a personcentered focus is consistent with previous literature used person-centered theories, such as Self-Determination Theory [3,4] and Transformational Leadership [10,12] to understand SCI peer mentorship. Our results also extend findings from a small body of research focusing on the perspective of the peer mentor where Gainforth et al [11] and Shaw et al [13] highlighted that effective peer mentors appear to adopt a person or client-centered approach.…”
Section: Discussionsupporting
confidence: 74%
“…As illustrated in recent reviews, multiple positive outcomes of receiving SCI peer mentorship have been reported, which include participation in daily and social activities, knowledge, sense of connection, and quality of life [8,9]. However, the majority of research on SCI peer mentorship has primarily focused on the experiences, outcomes, or preferences of this relationship from the perspective of the mentees [3,10], or from mixed STORIED EXPERIENCES OF SCI MENTORS 4 samples [11,12]. Although mentors play a prominent role in fostering the personal and professional well-being of mentees, few studies have focused solely on the perceptions of mentoring from the peer mentors [e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A negative outcome that was reciprocal for both mentors and mentees was a lack of connection. Sharing the same disability may not be sufficient for high quality mentorship experiences [ 27 ] and little research exists on the important matching criteria for peer mentorship relationships [ 28 ]. Recently, Gainforth et al described that matching characteristics should be more focused on interest and lived experience, which differs from traditional models matching on level of injury/sex [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was estimated based on the primary outcome measure (Moorong Self-Efficacy Scale [MSES] score) between the groups. In the study conducted by Martin et al [ 40 ], the mean difference in the MSES score at week 12 was normally distributed, with a mean of 1.95 and a standard deviation (SD) of 2.77. A total of 84 patients (42 patients in each group) were required for the study, with a two-tailed α of .05 and a power of 0.80.…”
Section: Methodsmentioning
confidence: 99%